HABITUAL PHYSICAL ACTIVITY AND MOTOR COORDINATION IN STUDENTS OF ELEMENTARY SCHOOL II (Fiep Bulletin - online, 2013)
Monitoring the levels of coordination and physical activity has become a topic widely discussed lately in the school context, since the arrival of new technologies such as video games and computer games, has been occupying the space of interest and physical education classes. This study aims to analyze the level of habitual physical activity and motor coordination of school in junior high school II. The research was descriptive and cross-sectional developmental design. The population was composed of students of both sexes enrolled from 8 th to 9 th year of elementary school II of private schools from Mater Christi Mossoró, State of RN. A sample of 55 students, 21 boys and 34 girls, selected in a probabilistic manner during physical education classes. The measurement instrument used was the questionnaire proposed Baeck et al. (1982) for obtaining the index of habitual physical activity (IAFH) was applied and the battery test motor coordination of KTK (Körperkoordinations test für kinder-KTK). To evaluate the relationship between physical activity and the level of coordination of the subjects was used Pearson linear correlation. The results showed that, regardless of gender, had a high proportion of sedentary young adults who do not meet daily physical activity, which may be a determining factor for the low level of motor coordination and the development of health problems. This suggests that children obtain a greater opportunity for leisure playground at home and at school.
Keywords: Everyday; teenager; habitual physical activity